Personality Disorder Traits, Trauma, and Risk in Perpetrators of Domestic Violence - Green, Kathleen (International journal of offender therapy and comparative criminology, 2020)
Crimes committed against partners and family members have devastating effects on victims. Unfortunately, recidivism rates for offenders are high, and there is a need to establish risk factors that may be potential treatment targets. This study aimed to investigate childhood maltreatment, symptoms of trauma, and personality disorder (PD) traits in males convicted of domestic violence (DV) offences. Data were extracted from the files of 40 males under the supervision of the probation service in the United Kingdom. Actual return to custody was recorded after a minimum follow-up of 6 months. Self-reported childhood maltreatment was associated with increases in PD traits, posttraumatic symptoms, and assessed risk. However, maltreatment did not predict return to custody. Tension-reducing behaviours and depressive symptoms predicted return to custody as did antisocial PD. These preliminary findings highlight important areas of future research, in particular, factors which may be relevant treatment targets in reducing the risk of recidivism.